Stochastic fracture generation accounting for the stratification orientation in a folded environment based on an implicit geological model - Borghi, Andrea; Renard, Philippe; Fournier, L; Negro, François (My University, 2015)
This paper presents a new approach in generating stochastic discrete fracture networks. The particularity of the approach is that it allows us to simulate the theoretical families of fractures that are expected in a folded environment. The approach produces fractures that are consistent with the local stratigraphic orientation. The fractures are modeled as simple rectangular planar objects. When they are modeled, they are rotated according to the local stratigraphic orientation. As the stratigraphy is modeled using an implicit approach, we use the gradient of this geological potential ﬁeld to retrieve the information about the geological orientation. The fracture number and size are following user-deﬁned probability density functions.
Keywords: Geological modeling; Discrete fracture network (DFN); Stochastic modeling; Structural geology